Does the benthic biota or fish assemblage within a large targeted fisheries closure differ to surrounding areas after 12 years of protection in tropical northwestern Australia?. (August 2021) - Langlois, Tim J.; Wakefield, Corey B.; Harvey, Euan S.; Boddington, Dion K.; Newman, Stephen J.
Abstract: A large ( 2450 km 2 ) offshore ( 75 km) targeted fisheries closure (TFC) area was implemented on the North West Shelf of Australia (NWS) in 1998 as part of a suite of management controls to address overfishing concerns, and in the process to potentially mitigate any impacts of trawling to benthic habitats. Twelve years later, the benthic biota and fish assemblages in the TFC were assessed using stereo-video and compared with adjacent areas that have been consistently fished with a range of commercial fishing methods. The remote nature of the region has meant that these areas would be inaccessible to recreational fishers. After 12 years of protection there were significant differences between the TFC and comparable fished areas in both the composition and the height of biogenic structures, however the magnitude of these differences were subtle, except for branching soft corals, which were significantly taller in the TFC area. Despite the relatively young age of the TFC, significant differences in the fish abundance and biomass compositions were driven by the slower growing, longer lived and inherently less productive fishery target species. The abundance of Lutjanus sebae (red emperor) and Epinephelus multinotatus (Rankin cod), and the associated biomass of L. sebae and Pristipomoides multidens (goldband snapper) were all greater within the TFC. However, neither the abundance or biomass of the relatively shorter lived and more productive fishery species (e.g. the bluespotted emperor Lethrinus punctulatus and the brownstripe snapper Lutjanus vitta ) were greater within the TFC. Growth rates of benthic biota across the NWS are unknown, however the limited detectable differences in benthic biota between the TFC and fished areas, suggests that either recovery of the benthic biota is slow and may not yet be at a threshold for detection and/or alternatively that current fishing activities are not causing adverse impacts to biogenic structures. These large, offshore targeted fishery closures provide a useful reference point to examine the natural variability, growth and recovery of benthic biota and fish assemblages after the cessation of fishing. Highlights: Large offshore closure created in 1998 due to overfishing concerns in NW Australia. Recovery rate after trawling in deeper water tropical regions is unknown. After 12 years only subtle change in benthic biota, but taller branching soft coral. After 12 years differences in the fish were driven by longer lived target species.